Coughing Shih Tzu dog due to myxomatous mitral valve disease stage C2 - Bay, Jessie Ji Xi; Khor, Kuan Hua (Veterinary Association Malaysia, 2018)
Myxomatous Mitral Valve Disease is a degenerative condition of the mitral valves leaflets. A 10-year-old male castrated Shih Tzu was presented with primary complaint of coughing. Clinical examination revealed normal heart rate, respiratory rate and rectal temperature. Systolic murmur Grade IV/VI was heard at the left heart apex. Thoracic radiographic findings were cardiomegaly with the vertebral heart score of 11.0 and had evidence of cardiogenic pulmonary edema. Echocardiographic examination revealed thickening mitral valves with evidence of moderate regurgitation observed. Based on the findings obtained, the dog was diagnosed with Myxomatous Mitral Valve disease stage C2. Dog was treated with benazepril (0.5mg/kg), pimobendan (0.2mg/kg) with a combination of furosemide (2mg/kg). Frusemide was gradually removed from the treatment regime as coughing improved over time. The dog was no longer lethargy and even gained weight.